2006
DOI: 10.24200/tjer.vol3iss1pp75-78
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pavement Skid Resistance on Traffic Accidents

Abstract: The Ministry of Transport (MOT) in the Kingdom of Saudi Arabia had collected a massive amount of friction measurements using a Mu-meter covering most of the major highway network in the kingdom. Traffic accident data of 89 high accident rate locations from four main different highway classes were extracted from the MOT accident records. Pavement skid resistance for the selected locations was determined from the pavement skid resistance records. The objective of this paper is to utilize these data to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Kuttesch showed skid resistance to be a significant factor in modeling wet accident rates in Virginia (6). Al-Mansour showed that pavements with FN values below 35 had the highest accident rates (7). Those rates stabilized as FN exceeded 45.…”
Section: Crash Analysismentioning
confidence: 96%
“…Kuttesch showed skid resistance to be a significant factor in modeling wet accident rates in Virginia (6). Al-Mansour showed that pavements with FN values below 35 had the highest accident rates (7). Those rates stabilized as FN exceeded 45.…”
Section: Crash Analysismentioning
confidence: 96%
“…In Saudi Arabia Al-Mansour [24] investigated the effects of pavement skid resistance on traffic accidents. The analysis included establishing relationships between skid resistance and accident number, accident significance and accident density.…”
Section: Evaluation Of Previous Studies and The Importance Of Skid Rementioning
confidence: 99%
“…A critical value of skid resistance was also established based on number, significance and density of accidents. As Al-Mansour [24] indicated, there are no standards agreed upon which define minimum acceptable skid resistance levels. Several studies have been conducted to develop criteria for critical skid resistance levels.…”
Section: Evaluation Of Previous Studies and The Importance Of Skid Rementioning
confidence: 99%
“…Wet pavement accidents and a total number of accidents were used to study the relationships between MATEC Web of Conferences 192, 02049 (2018) https://doi.org/10.1051/matecconf/201819202049 ICEAST 2018 pavement skid resistance and a total number of wet pavement accidents on major highways in the Kingdom of Saudi Arabia [7]. It was concluded that the number of accidents approaches almost a constant number at a skid number greater than 0.45.…”
Section: Road Accident and Skid Resistancementioning
confidence: 99%